From Sacred and Profane to Spiritual Space: How the Rise of Spirituality in the Late Twentieth Century Transformed Spatial Power and Reinterpreted Christian Space - Kilde, Jeanne Halgren (Studia liturgica, 2026)
This article offers a brief historical and semantic overview of the twentieth-century development of four key concepts central to the study of religious space - "sacred," "profane," "sacred space," and "spirituality" - with an emphasis on the attendant changes in the general experience of power within Christian churches that accompanied these conceptual revisions. Drawing attention to the positionality of scholars involved in the semantic variations, the article outlines some of their socio-religious concerns and argues those circumstances be considered when the terms are now used by scholars. Regarding power, the article maintains that while historically Christian insiders emphasized divine power and academic scholars explored social power within churches, the recent popularization of personal power in the form of "spirituality" has revised the concept of "sacred space" once again, resulting in the current use of spirituality as the primary evaluative criteria for church architecture.